1994
DOI: 10.3177/jnsv.40.371
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression by Cofactors Derived from B Vitamins.

Abstract: SummaryVitamins represent precursor molecules for the majority of cofactors essential for various enzyme activities. Is the expression of proteins that require a specific cofactor for their function correlated to its availability? Examples are presented and discussed of the involvement of vitamin-derived cofactors in the regulatory mechanisms controlling gene expression in bacteria and eukaryotes at the transcriptional and trans lational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 129 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Examples are the lipophilic vitamins A and D that serve as ligand precursors of the hormone nuclear receptors superfamily and thus affect systemic functions [1][2][3]. Although little is known about watersoluble vitamins as genetic modulators, there is increasing number of examples of their effects on gene expression [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Examples are the lipophilic vitamins A and D that serve as ligand precursors of the hormone nuclear receptors superfamily and thus affect systemic functions [1][2][3]. Although little is known about watersoluble vitamins as genetic modulators, there is increasing number of examples of their effects on gene expression [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Increasing knowledge on the molecular mechanisms of these vitamins has opened new perspectives that form a connection between nutritional signals and the development of new therapeutic agents [5,6]. Although little is known about water-soluble vitamins as genetic modulators, there are increasing examples of their effects on gene expression [7][8][9].…”
mentioning
confidence: 99%
“…Interestingly, it has been demonstrated that some of B vitamins also participate in the regulation of gene expression (Brandsch 1994). Recently, Liu and Zempleni (2014) reported that vitamin B 2 deficiency changed the expression pattern of pro-inflammatory genes through a loss of lysine-specific demethylase 1 activity in human T Lymphoma Jurkat cells.…”
mentioning
confidence: 99%